2008
DOI: 10.1590/s0103-97332008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Wang-Landau simulations of a simple continuous homopolymer

Abstract: The Wang-Landau method is used to study thermodynamic properties of a three-dimensional flexible homopolymer chain with continuous monomer positions. Results describing the coil-globule and solid-liquid transitions are presented for chain lengths up to N = 100. In order to elucidate the thermodynamic behavior, finite chain length effects and the influence of the energy range over which the density of states is determined are carefully analyzed. Simulation efficiency is also studied and it is shown that setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…8 The transitions of single untethered polymer chains have been investigated intensively with a variety of offlattice polymer models. 30,31,44,45,46,47,48,49,50,51 Except for the shortest chains and the most short-ranged interactions, the heat capacity as a function of temperature shows two prominent features; a peak at higher temperatures that indicates the transition from disordered coil conformations to disordered globule conformations, and a peak at low temperatures that indicates the transition from a liquid-like disordered globule to a solid-like ordered globule. Typically, the peak associated with the order-disorder transition, which is sometimes referred to as the "freezing" transition, sharpens with increasing chain length and is accompanied by a bimodal probability distribution as expected for a discontinuous transition.…”
Section: Chain Collapse For a Hard Surfacementioning
confidence: 99%
“…8 The transitions of single untethered polymer chains have been investigated intensively with a variety of offlattice polymer models. 30,31,44,45,46,47,48,49,50,51 Except for the shortest chains and the most short-ranged interactions, the heat capacity as a function of temperature shows two prominent features; a peak at higher temperatures that indicates the transition from disordered coil conformations to disordered globule conformations, and a peak at low temperatures that indicates the transition from a liquid-like disordered globule to a solid-like ordered globule. Typically, the peak associated with the order-disorder transition, which is sometimes referred to as the "freezing" transition, sharpens with increasing chain length and is accompanied by a bimodal probability distribution as expected for a discontinuous transition.…”
Section: Chain Collapse For a Hard Surfacementioning
confidence: 99%
“…In the microcanonical analysis, the temperature is defined via the curvature of the caloric entropy curve and thus all transition signals in the microcanonical entropy can be directly associated with a transition temperature.After introducing the method, we apply it to liquidsolid and solid-solid transitions occurring for elastic, flexible polymers, which have been under debate for quite some time. In contrast to the rather well-understood coil-globule collapse transition, the formation of highly compact crystalline, amorphous, or glasslike structures intricately depends on the precise relation of intrinsic energy and length scales in the system [4][5][6][7][8][9].In recent work, the microcanonical analysis has successfully been applied in aggregation studies of coarsegrained polymer and peptide models, where a nucleation process was found to be an energetically ordered hierarchy of individual structural subphase transitions [10]. Caloric approaches have also been used to investigate the folding behavior of proteins [11][12][13][14][15] and the structural phases of polymers with stiff bonds [8], as well as polymer adsorption transitions [16][17][18].…”
mentioning
confidence: 99%
“…We employ a coarse-grained off-lattice model for a single elastic flexible homopolymer [17][18][19][20][21] consisting of N = 13 monomers [22]. All monomers interact pairwise via a LennardJones (LJ) potential V pp LJ (r) = 4 pp [(σ/r) 12 − (σ/r) 6 ],…”
Section: A Compound Polymer-membrane Modelmentioning
confidence: 99%